PENGARUH KUALITAS KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PERSONEL POLRI PADA LEMBAGA PENDIDIKAN SEKOLAH POLISI NEGARA (SPN) BATUA POLDA SULAWESI SELATAN - Harmawan, Esa Florestha Ramadhani; Nurakhim, Bambang; Nengsih, Widya (Journal MISSY (Management and Business Strategy), 2025)
Work quality is the level achieved from the process or results obtained in an activity approaching perfection. Work motivation is the driving force for someone to make the greatest possible contribution for the success of the organization in achieving its goals. Performance is the result of work that can be achieved by a person or Police Personnel in carrying out their duties in an organization. The objectives of the study are as follows: To determine whether together the influence of Work Quality and Work Motivation on the Performance of Police Personnel at the Batua State Police School (SPN) of South Sulawesi Regional Police The sampling technique used in this study the author used the Random Sampling technique or randomly from the existing population of 166 people, the population used as a sample refers to the Slovin formula in Husein Umar, 2017, 62 samples were obtained. Based on the calculation results of the data, the positive influence of Work Quality on the Performance of Police Personnel was obtained with a partial value of 0.918, meaning there is a very strong influence or influence with a coefficient of determination of 84.3%. This is proven by the hypothesis test of the Work Quality variable on the Performance of Police Personnel, the value of to = 13.352> t0.05 (61) = 1.670, so Ho is rejected and Ha is accepted, meaning there is a very significant influence. Based on the calculation results, there is a positive influence of Work Motivation on the Performance of Police Personnel, the partial value of 0.843 is obtained, meaning there is a very strong influence or influence with a coefficient of determination of 71.1%. This is proven by the hypothesis test of the Work Motivation variable on the Performance of Police Personnel, the value of to = 6.917> t0.05 (61) = 1.670, so Ho is rejected and Ha is accepted, meaning there is a significant influence. Simultaneously there is a positive influence of the variables of Work Quality and Work Motivation on the variable of Police Personnel Performance with a simultaneous correlation value or Model Summary producing an R value of 0.916 and while the R Square value is 0.839 or 83.9%, this can be stated that the results of the analysis together the variables of Work Quality and Work Motivation on the variable of Police Personnel Performance have a very strong influence. Proven through the results of the F test (ANOVA) or F count obtained a value of 382,889 which is greater than F table (62) of 2.760 with a significant level of 0.000 because 0.000 <0.05, then it can be said that the variables of Work Quality and Work Motivation together or simultaneously on Police Personnel Performance have a very significant influence.